Ependymal Cells Require Anks1a for Their Proper Development - Park, Sunjung; Lee, Haeryung; Lee, Jiyeon; Park, Eunjeong; Park, Soochul (Molecules and cells, 2019)
Ependymal cells constitute the multi-ciliated epithelium, which lines the brain ventricular lumen. Although ependymal cells originate from radial glial cells in the perinatal rodent brain, the exact mechanisms underlying the full differentiation of ependymal cells are poorly understood. In this report, we present evidence that the Anks1a phosphotyrosine binding domain (PTB) adaptor is required for the proper development of ependymal cells in the rodent postnatal brain. Anks1a gene trap targeted LacZ reporter analysis revealed that Anks1a is expressed prominently in the ventricular region of the early postnatal brain and that its expression is restricted to mature ependymal cells during postnatal brain development. In addition, Anks1a-deficient ependymal cells were shown to possess type B cell characteristics, suggesting that ependymal cells require Anks1a in order to be fully differentiated. Finally, Anks1a overexpression in the lateral wall of the neonatal brain resulted in an increase in the number of ependymal cells during postnatal brain development. Altogether, our results suggest that ependymal cells require Anks1a PTB adaptor for their proper development.